Ethics and the Economy: Food for Thought from the Medieval Debate on Money. Issue 3 (3rd July 2019) - Figuera, Stefano; Tortorella Esposito, Guido
Abstract: In the ethics-economy debate, money and credit have acquired growing significance. Moral judgements on some aspects of money and credit emerged particularly in the late medieval period when their development led the economic system towards capitalism. Scholarly Islamic and Christian analyses show that the evolution of money and credit may have triggered prejudices about the ethically-based rules underpinning the economy and society. Thought on the late medieval monetary and credit institutions highlight points of contact between Christian and Islamic ethical codes which are still of great interest, especially for the identification of a shared ethics going beyond business.